(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Foreign body aspiration (FBA) is a common condition with potential to cause significant morbidity and mortality. In children, highest incidence is within the first 3 years of life. Without witnessed aspiration or acute symptoms such as choking, coughing or respiratory distress, it may go unnoticed as clinical presentation and radiological investigations generally have low diagnostic value. Delay in diagnosis increases the risk of developing severe complications. Unexplained recurring or persistent lung pathologies in this age group should raise suspicion of FBA, and early bronchoscopy is warranted for confirmation of diagnosis. We report a case of FBA in a 2-year-old boy whom had been symptomatic for 3 months and was treated as bronchial asthma prior to diagnosis of foreign body in the left bronchus. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12017 Bangladesh J Otorhinolaryngol 2012; 18(2): 200-202